Bad Kitty joins the team - Bruel, Nick (New York : Roaring Brook Press, 2019)
Kitty is terribly out of shape and when Kitty's owner catches her wheezing, she is told that it is time to exercise, but it will take a lot of convincing and a bit of trickery to get Kitty into the competitive spirit.
3.1
K-3
GN490L
Keywords: Bad Kitty -- (Fictitious character from Nick Bruel) -- Juvenile fiction; Cats -- Juvenile fiction; Exercise -- Juvenile fiction; Sports -- Juvenile fiction; Bad Kitty -- (Fictitious character from Nick Bruel) -- Fiction; Cats -- Fiction; Exercise -- Fiction; Sports -- Fiction; Humorous fiction